COST-EFFICACY ANALYSIS OF GEFITINIB EFFICACY IN PATIENTS WITH NON OPERABLE NON SMALL CELL LUNG CANCER - S. A. Protsenko; A. V. Rudakova; F. V. Moiseyenko; E. V. Levchenko; D. E. Matsko; A. О. Ivantsov; I. I. Semenov; A. G. Ievleva; N. V. Mitushkina; A. V. Togo; A. V. Novik; E. N. Imyanitov; et al. (Креативная хирургия и онкология)
Drug treatment of disseminated non small cell lung cancer  (NSCLC) is an actual  issue today.  Both clinical and economic efficacy analysis is needed for optimal therapy selection. We performed economic efficacy assessment of  gefitinib (G.)  therapy in patients with non operable NSCLC who hase no EGFR mutation using Markov model based  on results of clinical studies  conducted in N.N. Petrov Research Institute of Oncology.G. increases  overall survival of patients with NSCLC with EGFR mutation by 1,05 year. Cost/efficacy coefficient for  G. in patients with  EGFR mutation is 934  800  rub  per  1 acquired year  of  life. Therapy  with  G just for  patients with  genetically  proven  mutation is dominating strategy when  compared to  therapy for  all NSCLC patients  irrespectively to  mutation status (saving  211600 – 251800  rub per  1  patient taking  into  account equal clinical efficacy). Therapy  with  G. is economically  justifying  strategy when  compared to chemotherapy (additional costs coefficient 960700 – 1010000 rub per 1 gained year of life). Thus, EGFR mutation testing with subsequent G. therapy in non  operable NSCLC patients not only prolongs patient’s life but also has  acceptable level of medical expenses.